Upaya Peningkatan Hasil Belajar Peserta Didik Melalui Metode Inkuiri dengan Media Konkret pada Mata Pelajaran Matematika di Kelas IV SDN Jajartunggal I/450 Surabaya Tahun Pelajaran 2021/2022 - Suparmiasih (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The background of this study comes from the low learning outcomes of students in Mathematics subjects in Class IV students of SDN Jajartunggal I/450 Surabaya. The low learning outcomes are due to inappropriate learning methods, low interest and motivation of students to learn, lack of active participation of students in the learning process and learning methods that are not fun according to the age of grade IV elementary school students, so that the material is not absorbed perfectly. The purpose of this study was to improve math learning outcomes in Class IV students of SDN Jajartunggal I/450 Surabaya, and increase the activeness of students in the learning process. This research uses the inquiry method assisted by concrete media. It aims to improve the learning outcomes of students, increase the activeness of students in learning and make the learning process fun and help students' memory be absorbed longer through real or concrete media. The result of the research is the increase in learning outcomes and student activeness. This can be seen from the analysis of the value in the pre-cycle of learning completeness reached 30.30%, the class average reached 62.22 and the activeness of students reached 30.5%. In cycle I, learning completeness rose to 81.48%, the class average also rose to 71.48 and the activeness of students reached 50%. In cycle II, learning completeness increased from cycle I, namely 92.59%, the class average also increased to 71.48 and learner activeness reached 50%. In cycle II, learning completeness increased from cycle I, namely 92.59%, the class average rose to 78.15 and student activeness increased to 72.2%. The research target in improving the learning outcomes of Mathematics addition competency is that the teacher invites the active role of students in the form of groups in fun learning through inquiry methods assisted by real or concrete objects, and audio-visual media so as to achieve satisfactory learning outcomes.